2011
DOI: 10.1007/s10072-011-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid attenuates oxidative stress on brain and sciatic nerve and improves histopathology of brain in streptozotocin-induced diabetic rats

Abstract: The aim of this study was to investigate the possible effects of ellagic acid in brain and sciatic nerve tissues of diabetic rats. Also, the impact of ellagic acid on catalase and paraoxonase (PON-1) activities, total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), malondialdehyde (MDA) and nitric oxide (NO) were examined. The rats were randomly divided into four groups, with eight rats each: Normal controls (not diabetic), only ellagic acid treated (ellagic acid controls, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…With respect to numerous reports in antioxidant role of EA on neuodegeneration [47][48][49][50], we can confirm anti-oxidative profile of EA. The SOD enzyme produces substrate for GPx activity in the brain under stressful situations [51,52].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…With respect to numerous reports in antioxidant role of EA on neuodegeneration [47][48][49][50], we can confirm anti-oxidative profile of EA. The SOD enzyme produces substrate for GPx activity in the brain under stressful situations [51,52].…”
Section: Discussionsupporting
confidence: 79%
“…However, the long-time study in reperfusion phase to show more specific role and perceive mechanism of EA effect should be designed in future studies. Several line of evidences consistently supports the claim that ellagic acid improves antioxidant enzymes and subsequently these enzymes might defend neuronal cells against produced free radicals in brain injuries [47,48,49]. Herein, we detected the two antioxidant enzymes (SOD and GPx) in the present or absence of ellagic acid in ischemic rats' tissues.…”
Section: Discussionsupporting
confidence: 77%
“…The TOS measurements provide a sensitive index of lipid peroxidation and oxidative stress. 23 In the kidney tissues and serum, we found that both the 50-mg and 100-mg ASA doses caused a significant increase in the TOS levels, which may be due to overproduction or decreased excretion of oxidant substances. We also found that the TAC levels and PON-1 activities decreased in the ASAadministered rats when compared with the controls.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, this compound has neuroprotective in focal cerebral ischemia, traumatic brain injury and also in brain histopathologic damage induced by streptozotocin in rats (Uzar et al 2012;Rafieirad & Ghasemzadeh-Dehkordi 2014;Farbood et al 2015).…”
Section: Discussionmentioning
confidence: 99%